Characterization of the A2AR-D2R interface: Focus on the role of the C-terminal tail and the transmembrane helices - Borroto-Escuela, Dasiel O.; Romero-Fernandez, Wilber; Tarakanov, Alexander O.; Gómez-Soler, Maricel; Corrales, Fidel; Marcellino, Daniel; Narvaez, Manuel; Frankowska, Malgorzata; Flajolet, Marc; Heintz, Nathaniel; Agnati, Luigi F.; Ciruela, Francisco; et al. (Elsevier, 2010)
A single serine point mutation (S374A) in the adenosine A2A receptor (A2AR) C-terminal tail reduces A2AR-D2R heteromerization and prevents its allosteric modulation of the dopamine D2 receptor (D2R). By means of site directed mutagenesis of the A2AR and synthetic transmembrane (TM) α-helix peptides of the D2R we further explored the role of electrostatic interactions and TM helix interactions of the A2AR-D2R heteromer interface. We found evidence that the TM domains IV and V of the D2R play a major role in the A2AR-D2R heteromer interface since the incubation with peptides corresponding to these domains significantly reduced the ability of A2AR and D2R to heteromerize. In addition, the incubation with TM-IV or TM-V blocked the allosteric modulation normally found in A2AR-D2R heteromers. The mutation of two negatively charged aspartates in the A2AR C-terminal tail (D401A/D402A) in combination with the S374A mutation drastically reduced the physical A2AR-D2R interaction and lost the ability of antagonistic allosteric modulation over the A2AR-D2R interface, suggesting further evidence for the existence of an electrostatic interaction between the C-terminal tail of A2AR and the intracellular loop 3 (IL3) of D2R. On the other hand, molecular dynamic model and bioinformatic analysis propose that specific AAR, AQE, and VLS protriplets as an important motive in the A2AR-D2LR heteromer interface together with D2LR TM segments IV/V interacting with A2AR TM-IV/V or TM-I/VII.
Keywords: Dopamina - Receptores; Dopamine D2 receptor; Adenosine A2A receptor; Heteromerization; G protein coupled receptors; Transmembrane segments; Protein–protein interaction